A2A adenosine receptor-driven cAMP signaling in olfactory bulb astrocytes is unaffected in experimental autoimmune encephalomyelitis - Wendlandt, Marina; Kürten, Alina J.; Beiersdorfer, Antonia; Schubert, Charlotte; Samad-Yazdtchi, Kiana; Sauer, Jessica; Pinto, M. Carolina; Schulz, Kristina; Friese, Manuel A.; Gee, Christine E.; Hirnet, Daniela; Lohr, Christian (Frontiers in Immunology, 2023)
The cyclic nucleotide cyclic adenosine monophosphate (cAMP) is a ubiquitous second messenger, which is known to play an important anti-inflammatory role. Astrocytes in the central nervous system (CNS) can modulate inflammation but little is known about the significance of cAMP in their function. We therefore investigated cAMP dynamics in mouse olfactory bulb astrocytes in brain slices prepared from healthy and experimental autoimmune encephalomyelitis (EAE) mice. The purinergic receptor ligands adenosine and adenosine triphosphate (ATP) both induced transient increases in cAMP in astrocytes expressing the genetically encoded cAMP sensor Flamindo2. The A2A receptor antagonist ZM241385 inhibited the responses. Similar transient increases in astrocytic cAMP occurred when olfactory receptor neurons were stimulated electrically, resulting in ATP release from the stimulated axons that increased cAMP, again via A2A receptors. Notably, A2A-mediated responses to ATP and adenosine were not different in EAE mice as compared to healthy mice. Our results indicate that ATP, synaptically released by afferent axons in the olfactory bulb, is degraded to adenosine that acts on A2A receptors in astrocytes, thereby increasing the cytosolic cAMP concentration. However, this pathway is not altered in the olfactory bulb of EAE mice.